2017
DOI: 10.5296/jpmr.v3i1.11191
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Illegal Payments in Greece

Abstract: The phenomenon of corruption is global and extends in many areas of the public sector. However, in Greece it appears to be socially acceptable since in the case of illegal benefits and pensions, the corruption of the public officials takes place with the collaboration of the ISSN 2377-3294 2017 citizens who receive such pensions and allowances. It should be noted that in Greece the phenomenon has not been fully recorded since the only information available can be derived from the Press due to the publicity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The presence of an audit mechanism is deemed essential because, in Greece, corruption in public administration is identified as a pervasive issue stemming from a dysfunctional public sector (Zacharakis et al 2017). Under these circumstances, the state apparatus is highly inefficient and results in negative impacts at the economic and fiscal levels.…”
Section: Understanding the Variablesmentioning
confidence: 99%
“…The presence of an audit mechanism is deemed essential because, in Greece, corruption in public administration is identified as a pervasive issue stemming from a dysfunctional public sector (Zacharakis et al 2017). Under these circumstances, the state apparatus is highly inefficient and results in negative impacts at the economic and fiscal levels.…”
Section: Understanding the Variablesmentioning
confidence: 99%
“…The available data however in conjunction with a wealth of Greek and international research evidence (e.g. Cuervo-Cazurra 2016; Zacharakis et al 2017) indicated clearly that the encounter of hotel GMs with corruption influenced to a certain degree the manager's work.…”
Section: Factor 4: Dealing With Corruptionmentioning
confidence: 99%
“…Με τα παραπάνω χαρακτηριστικά το Ενιαίο Σχέδιο Δράσης και Διατήρησης της Επιχειρησιακής Συνοχής δίνει έμφαση στην πρόληψη και την αντιμετώπιση των έκτακτων καταστάσεων και κρίσεων, στην εφαρμογή μοντέλων διαχείρισης ανθρώπινου δυναμικού ικανού να αντεπεξέλθει σε αυτές τις ανάγκες επιτυγχάνοντας με τον τρόπο αυτό την αύξηση της εμπιστοσύνης του πολίτη στο κράτος στο κρίσιμο κομμάτι της κοινωνικής ασφάλισης, αλλά και την εύρυθμη λειτουργία των ασφαλιστικών οργανισμών (Zacharakis et al, 2017).…”
Section: εμπειρικεςunclassified